Electrode dependence in halide perovskite memories: resistive switching behaviours - Thien G.S.H.; Sarjidan M.A.M.; Talik N.A.; Goh B.T.; Yap B.K.; He Z.; Chan K.-Y. (Royal Society of Chemistry, 2023)
Light absorption; Perovskite; Absorption characteristics; Design structure; Halide perovskites; Laser lights; Lightemitting diode; Performance; Photovoltaics; Resistive switching; Resistive switching behaviors; Switching properties; Electrodes